Transkulturelle Verflechtungsprozesse in der Vormoderne - Drews, Wolfram; Scholl, Christian (Das Mittelalter. Perspektiven mediävistischer Forschung. Beihefte, 2016)
Pre-Modern Europe`s diverse ethnic and religious groups were in continuous contact with each other and also with "cultures" beyond Europe. This collected volume analyzes these reciprocal exchange processes, taking into consideration connections between Christians, Jews, and Moslems as well as relationships between Western Europe, the Byzantine Empire, the Near East, and India.